Disability and Health Problems as Barriers to Employment in Spain - Ponce-Caballero, María del Carmen; Caçador-Rodrigues, Leonel; Millán-Tapia, Ana; Millán-Tapia, José María (Revista de Estudios Andaluces, 2018)
This paper explores the role of different types of limitations, diseases and health problems on both the probability of working and the probability of belonging to different groups (entrepreneurs, civil servants, other paid employees, unemployed, inactive individuals and students). To this end, we apply binary and multinomial non-ordered discrete choice models to microdata drawn from the 2014 European Health Interview Survey for Spain. Our main results show that the probability of having a job is lower for those individuals with mental limitations or health problems. When distinguishing between groups, we see that neither physical nor mental limitations affect the probability of being a civil servant.